Dislocation arrangements in 4H-SiC and their influence on the local crystal lattice properties - Roder, Melissa; Steiner, Johannes; Wellmann, Peter; Kabukcuoglu, Merve; Hamann, Elias; Haaga, Simon; Hänschke, Daniel; Danilewsky, Andreas (Journal of Applied Crystallography, 2023)
Two wafers of one 4H-silicon carbide (4H-SiC) bulk crystal, one cut from a longitudinal position close to the crystal’s seed and the other close to the cap, were characterized with synchrotron white-beam X-ray topography (SWXRT) in back-reflection and transmission geometry to investigate the dislocation formation and propagation during growth. For the first time, full wafer mappings were recorded in 00012 back-reflection geometry with a CCD camera system, providing an overview of the dislocation arrangement in terms of dislocation type, density and homogeneous distribution. Furthermore, by having similar resolution to conventional SWXRT photographic film, the method enables identification of individual dislocations, even single threading screw dislocations, which appear as white spots with a diameter in the range of 10 to 30 mm. Both investigated wafers showed a similar dislocation arrangement, suggesting a constant propagation of dislocations during crystal growth. A systematic investigation of crystal lattice strain and tilt at selected wafer areas with different dislocation arrangements was achieved with high-resolution X-ray diffractometry reciprocal-space map (RSM) measurements in the symmetric 0004 reflection. It was shown that the diffracted intensity distribution of the RSM for different dislocation arrangements depends on the locally predominant dislocation type and density. Moreover, the orientation of specific dislocation types along the RSM scanning direction has a strong influence on the local crystal lattice properties.
CRIS-Team Scopus Importer:2024-12-16
Keywords: 4H-SiC; crystal growth; dislocations; high-resolution X-ray diffractometry; reciprocal-space maps; synchrotron white-beam X-ray topography